Fibrillar deformation mechanisms in rat Achilles tendons are governed by strain rate - Sharma, Kunal ; 0000-0003-3063-3709; Silva Barreto, Isabella ; 0000-0002-9413-8320; Dejea, Hector; Mota-Santiago, Pablo; Eliasson, Pernilla; Pierantoni, Maria ; 0000-0001-8362-9418; Isaksson, Hanna ; 0000-0002-9690-8907 (Acta Biomaterialia, 2025)
Tendons are hierarchically structured and composed of load-bearing collagen. Their hierarchical structure allows the transfer of tensile forces across multiple length scales as loads are partitioned from the whole tendon through fascicles, fibers, and fibrils down to the tropocollagen molecules. To elucidate their structural hierarchical deformation, this study investigated the combined tissue, fibrillar, and molecular response of tendons to in situ tensile load by means of simultaneous small- and wide-angle X-ray scattering. Rat Achilles tendons were loaded at three magnitudes of strain rates in ramp (20, 2, and 0.2 %/s), and 20 %/s in stress-relaxation for 500 s. Hierarchical strain partitioning was found, where in the 20 %/s strain rate group the fibrils were experiencing at most 7 % of the applied tissue strains, and molecules at most 2 %. At low and medium strain rates the fibrils elongated, while at the high strain rate the fibrils both elongated and slid, as observed by increase in d-spacing and decrease in overlap length. During stress relaxation, the fibril and molecular fast relaxation was four times slower compared to the overall tissue response. The fibrillar Poisson's ratios did not appear to change with strain rate. This study highlights how the viscoelastic behavior of tendons extends across length scales and provides further evidence of tendon's strain partitioning and strain-rate dependent deformation mechanisms. Statement of significance: Achilles tendons are exposed to high mechanical loads and are prone to injuries. Due to their hierarchical structure understanding how the loading is taken up by the tissue is complex. However, understanding the hierarchical structural response and its relation to tendon function is crucial to aid in rehabilitation and treatment. We combine the use of synchrotron small- and wide-angle X-ray scattering with simultaneous in situ loading of rat Achilles tendons to understand the relation between the loading of the whole tendon down to the structural adaptations of the collagen fibrils and collagen molecules, experienced at the nano- and ångstrom-scale. The proposed methodology aids in understanding the deformation mechanisms occurring during tendon loading and rupture.
Keywords: Collagen; In situ loading; Nanomechanics; SAXS; Strain rate; WAXS